Modeling of Plastic Debris Particle Trajectory During Pre and Post Reclamation in Jakarta Bay - Edwin Apriyanta Winardi; Mutiara Rachmat Putri; Muhammad Reza Cordova; Agus Setiawan (Politeknik Kelautan dan Perikanan Dumai, 2021)
The primary source of environmental problems in Jakarta Bay’s waters is the change in hydrodynamics caused by reclamation and land-derived waste from the 13 watersheds that discharge into the bay. In June and December 2006 and 2015, hydrodynamic and trajectory simulations were conducted in Jakarta Bay to determine the distribution of plastic debris in pre- and post-reclamation conditions. The hydrodynamic conditions and particle trajectory in Jakarta Bay were described numerically using the Hamburg Shelf Ocean Model (HAMSOM). Secondary tidal data and primary ADCP data are used to validate the simulation results. The distribution of plastic debris released during the simulation depicts a distribution that follows the monsoon pattern, moving west during the east monsoon and moving east in the west monsoon and spreading along the coastline in both conditions. The percentage of plastic debris increased by 21.42% in June and 4.07% in December. The increase in the percentage of plastic debris that remains in the waters of Jakarta Bay is due to a 0.03 - 0.05 m/s decrease in current velocity following the formation of the reclamation island. Due to the decrease in current velocity within the bay, trajectory simulations indicate that plastic debris will take an additional 69.52 – 304.25 hours to exit. The accumulation of plastic debris around the reclamation islands demonstrates that the islands act as waste traps, necessitating proper waste cleanup, particularly in the canal area and around the reclamation island.